2014
DOI: 10.15306/mvpjms/2014/v1i2/52026
|View full text |Cite
|
Sign up to set email alerts
|

Role of Synbiotics in Improvement of Feed Tolerance and Weight Gain in the Newborns

Abstract: Objective: To study the effect of Synbiotics on weight gain and feed tolerance of newborns. Methods: This prospective interventional trial included 50 newborns treated with a dietary supplement containing Synbiotics in addition to the routine treatment and 48 newborns served as control without Synbiotics supplement. The primary outcome was weight gain and feed tolerance. Results: Newborns in the Synbiotics group reached the full feeds earlier as compared to those in Control group (7.5 ± 4.26 days Vs 14.02 ± 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The study by Hartel et al showed that infants treated with probiotics had improved daily weight gain (20.8±6.6 vs 22.2±5.2, p<0.001). 17 Ravindra Sonawane et al observed better weight gain among newborns receiving synbiotics (14.61±9.6 grams per day vs 2.97±3.81 grams per day, p=0.0000001) 18.…”
mentioning
confidence: 97%
“…The study by Hartel et al showed that infants treated with probiotics had improved daily weight gain (20.8±6.6 vs 22.2±5.2, p<0.001). 17 Ravindra Sonawane et al observed better weight gain among newborns receiving synbiotics (14.61±9.6 grams per day vs 2.97±3.81 grams per day, p=0.0000001) 18.…”
mentioning
confidence: 97%